Longitudinal study of cognitive dysfunction in multiple sclerosis: neuropsychological, neuroradiological, and neurophysiological findings. Issue 7 (1st July 2003) - Piras, M R; Magnano, I; Canu, E D G; Paulus, K S; Satta, W M; Soddu, A; Conti, M; Achene, A; Solinas, G; Aiello, I
Abstract : Objective: (1) To assess cognitive function and cerebral magnetic resonance imaging (MRI) involvement in relapsing-remitting multiple sclerosis; (2) to monitor disease evolution, cognitive dysfunction, and cerebral lesion burden over time (mean 8.5 year follow up period); (3) to study the relation between clinical, neuropsychological, and MRI data. On follow up assessment, visual and auditory oddball event related potentials (ERPs) were recorded as psychophysiological evaluation of cognitive status. Correlations between neuropsychological, MRI, and ERP data were also analysed. Methods: Neuropsychological study assessed verbal and non-verbal IQ, deterioration index (DI) from WAIS subtests, conceptual reasoning, attention, verbal and visuospatial short-term and long term memory. MRI assessment detected presence of demyelinating lesions by using a semiquantitative method as well as cortical and subcortical atrophy over time. Results: Attention, short-term and long term visuospatial memory were mildly impaired at baseline and remained unaltered longitudinally. At retesting a significant worsening of verbal long term memory (p=0.023), DI presence (p=0.041) and the increase of supratentorial and subtentorial MRI lesions load (p=0.001) emerged. Expanded disability status scale score correlated significantly with total lesion burden at both evaluations (p=0.043 and p=0.024 respectively). Temporal, occipital, and frontal horn lesions as well as cortical atrophy correlated significantly with attention and memory tests at baseline. Follow up assessment revealed significant correlation between cortical atrophy and attention as well as visuospatial short-term memory; spatial long term memory correlated significantly with lesions in body of lateral ventricle and frontal lobe. ERP study showed P300 latency abnormalities in 75% of patients, involving specifically more visual P300 (58.4 % of cases) than auditory wave (41.6 %). Visual P300 latency and amplitude correlated significantly with DI and auditory P300 latency with frontal horn and brain stem lesions. Conclusions: These findings revealed mild cognitive impairment in MS patients particularly consistent with slowing information processing over time. Increased MRI lesions do not correlate with the clinical course of the disease and cognitive deficit evolution. Thus, cognitive dysfunction could be related to disease peculiarity and not to the time course. Correlations between P300, neuropsychological, and MRI findings provide further information about ERP application to examine cognitive impairment in MS and probably to investigate their neural origin.